Penguatan Literasi Gizi Anggota Kelompok Wanita Tani Panca Warna dalam Pencegahan Stunting Berbasis Pangan Lokal Kacang Buncis - Mardiana; Hayati; Muktasam; Daeva Mubarika Raisa (Universitas Mataram, 2026)
Stunting remains a serious chronic nutritional challenge in East Lombok Regency, West Nusa Tenggara. This community service activity aims to improve the nutritional literacy of Panca Warna Women Farmers Group (KWT) members in Bantek Hamlet, Sembalun Timba Gading Village, Sembalun District, in stunting prevention through the utilization of local green bean-based food. The method used is community education with a participatory approach through socialization, training, and group discussions. An initial knowledge assessment was conducted on 19 KWT members using a 10-item multiple-choice pretest covering stunting, the role of KWT, green bean potential, flour processing technology, and product marketing. Pretest results showed an average score of 8.47 out of 10. A total of 73.7% of respondents scored ≥8, indicating strong baseline knowledge. Key weaknesses were identified in group management and nutrition-based product marketing. This activity is expected to strengthen the institutional capacity of KWT as a local actor in reducing stunting prevalence.